73.0k views
3 votes
5/7^3 = 5(7^x)
Thank you for helping!!

User Fergusmac
by
4.8k points

1 Answer

3 votes

When solving this equation you get x = -3.

To solve this, simply follow the order of operations for solving.


(5)/(7^(3)) = 5(7^(x) ) ----> start by dividing both sides by 5


(1)/(7^(3)) = (7^(x) ) -----> Now you can transform the front side of the equation to use negative exponents.


7^(-3) = 7^(x)

Since both x and -3 are the powers of x, we can eliminate the 7 and just make the exponents equal.

-3 = x

User Msanford
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.